Perceived employability and career adaptability of engineering graduates - Monteiro, Sílvia (2021)
The new demands of the labor market have led to the emergence of more comprehensive and complexes employability models, including not only a set of skills determining employability but also a subjective dimension that integrates personal beliefs and attitudes. Besides that, there is also evidence that individuals' psychological resources, namely in terms of career adaptability, are significantly associated with further employability. In this paper, we present data on the perceptions of employability (four dimensions: my university, my study field, the labor market, and self-efficacy) and on the adaptability resources (concern, control, curiosity and confidence) of master's final-year students (n=362), comparing a group of engineering students with students from other study fields (Social Sciences and Humanities and Economics). Regarding the perceptions of employability, the obtained results demonstrate that engineering graduates present more positive perceptions in the dimensions of study field and of external labor market, comparing with their colleagues from other fields. Concerning career adaptability resources, the differences are reversed, with engineering students with scoring lower in the dimensions of concern and confidence.